2018
DOI: 10.12688/wellcomeopenres.14767.1
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory validation and field usability assessment of a point-of-care test for serum bilirubin levels in neonates in a tropical setting

Abstract: Background: Screening and monitoring serum bilirubin (SBR) in neonates is crucial to prevent neonatal hyperbilirubinemia (NH)-associated morbidity and mortality worldwide. A lack of resources is often a barrier for measuring SBR in developing countries. Reliable, cost-effective, easy to use point-of-care (POC) SBR tests are needed. This study aimed to evaluate the technical accuracy and usability of the Bilistick System (BS), a new bilirubin POC test, in a tropical setting. Methods: This was a mixed-methods st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 27 publications
(36 reference statements)
1
19
1
Order By: Relevance
“…The Bilistick ® underestimated TSB with an MD (±SD) of −22 (±39) µmol/L, with corresponding LoA from −100 to 56 µmol/L. Falsely low Bilistick ® values have been documented in a large study in 4 different countries that its performance [22]. This study confirmed that Bilistick ® values slightly underestimate TSB (−17 µmol/L over a TSB range from 17 to 684 µmol/L).…”
Section: Discussionsupporting
confidence: 76%
“…The Bilistick ® underestimated TSB with an MD (±SD) of −22 (±39) µmol/L, with corresponding LoA from −100 to 56 µmol/L. Falsely low Bilistick ® values have been documented in a large study in 4 different countries that its performance [22]. This study confirmed that Bilistick ® values slightly underestimate TSB (−17 µmol/L over a TSB range from 17 to 684 µmol/L).…”
Section: Discussionsupporting
confidence: 76%
“…8 Furthermore, we found that the mean difference in TSB between the two methods was much larger in our study (26.5 µmol/L) than those reported by Coda Zabetta (10 µmol/L) 8 and Thielemans (20 µmol/L). 13 One possible explanation could be the difference in sample sizes, as both of them had much smaller sample sizes than ours. We also did not measure the hematocrit nor the humidity in this study which Thielemans et al 13 showed that these could affect the accuracy of Bilistick readings.…”
Section: Discussionmentioning
confidence: 70%
“…13 One possible explanation could be the difference in sample sizes, as both of them had much smaller sample sizes than ours. We also did not measure the hematocrit nor the humidity in this study which Thielemans et al 13 showed that these could affect the accuracy of Bilistick readings.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations